Anti-macrophage migration inhibitory factor (MIF) activity of ibudilast: A repurposing drug attenuates the pathophysiology of leptospirosis. (December 2022) - Sumaiya, Krishnamoorthi; Selvambika, Panneerselvam; Natarajaseenivasan, Kalimuthusamy
Abstract: To develop the macrophage migration inhibitory factor (MIF) directed therapeutic approach for the treatment of leptospirosis, we identified potential MIF inhibitors by screening 10 essential tautomerase inhibition classes of chemical compounds and 7 existing anti-inflammatory and anti-microbial drugs. Dopachrome tautomerase assay was performed to measure the anti-MIF activity of selected compounds. Among 17 chemical compounds, ibudilast, an anti-inflammatory agent showed the MIF tautomerase IC50 value at a very lower concentration (9.5 ± 5.6 μM) which is considered similar to the IC50 of standard MIF antagonist, ISO-1 (6.2 ± 3.8 μM) with non-significant cytotoxicity. The in vitro analysis of the therapeutic potential of MIF inhibitor revealed that ibudilast significantly reduced the leptospiral lipopolysaccharide (LPS) mediated expression of inflammatory mediators such as intercellular adhesion molecule (ICAM), p38 and p44/42 mitogen-activated protein kinase (MAPK), inflammatory cytokines, and decreased the reactive oxygen species (ROS) production, mitochondrial membrane potential (ΔΨm ) loss and cell death of LPS treated THP-1 cells. In vivo analysis demonstrated that the administration of anti-MIF Ibudilast significantly reduced the histopathological changes, downregulates the pro-inflammatory cytokines, and protects the leptospiral BALB/c model from lethality by increasing the survival rate from 25% to 66%. Finally, the biocompatibility of the evaluated anti-MIF compound was explored by cytotoxicity, hemocompatibility, and cell death assay. Ibudilast showed no significant cytotoxicity and hemolytic activity was noticed even at the higher concentration of ≤50 μM and ≥250 μM, when compared with the positive control, 0.1% Triton X-100; no significant cell death was observed at ≤50 μM concentration of Ibudilast in THP-1 cells. From these lines of evidence, we propose that Ibudilast may be a great MIF targeting repurposing drug for reliable supportive treatment of severe leptospirosis. Highlights: Anti-MIF activity of Ibudilast (IC50 ) is considerably similar to the IC50 of standard MIF antagonist, ISO-1. Ibudilast downregulated the expression of inflammatory mediators and mitigates the pathophysiological effects. Ibudilast showed no significant cytotoxicity, red blood cell lysis, and cell death at the higher concentration of ≤50 μM. Ibudilast may be a great MIF targeting repurposing drug for reliable supportive treatment of severe leptospirosis.